Three-dimensional assessment of external apical root resorption after maxillary posterior teeth intrusion with miniscrews in anterior open bite patients - Bilal Al-Falahi; Ahmad Mohammad Hafez; Maher Fouda
ABSTRACT Objective: The objective of this study was to assess the external apical root resorption (EARR) of the maxillary posterior teeth after intrusion with miniscrews. Methods: Fifteen patients (13 females and 2 males) with age ranging from 14.5 to 22 years (mean 18.1 ±2.03 years) were selected to participate in this study. All patients presented with anterior open bite of 3 mm or more. An intrusion force of 300 g was applied on each side to intrude the maxillary posterior teeth. Cone beam computed tomography (CBCT) scans were taken pretreatment and post-intrusion and were analyzed to evaluate the EARR. Results: The maxillary posterior teeth were intruded in average 2.79 ± 0.46 mm (p< 0.001) in 5.1 ± 1.3 months, and all examined roots showed statistically significant EARR (p< 0.05) with an average of 0.55 mm, except the distobuccal root of the left first permanent molars and both the palatal and buccal roots of left first premolars, which showed no statistically significant changes. Conclusions: The evaluated teeth presented statistically significant EARR, but clinically, due to the small magnitude, it was not considered significant. Moreover, the CBCT provided a good visualization of all roots in all three planes, and it was effective in detecting minimal degrees of EARR.